Ratios of forces and forces moments as dynamic similarity criteria of various phenomena occurring in wind engineering, snow engineering and fluid dynamics: Part II – Unsteady problems of periodic, quasi-periodic and turbulent character - Flaga, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2019)
The work concerns dynamic similarity criteria of various phenomena occur-ring in wind engineering, snow engineering and fl uid dynamics derived from ratios of forces and forces moments affecting these phenomena. Derived and analyzed in part II dynamic similarity criteria, mainly concern the following unsteady problems of periodic, quasi-perio-dic and turbulent character: 1. Vibrations of a solid in a stationary and moving fl uid; 2. Snow particles/fl akes/clusters breaking off the outer layer of the snow deposit; 3. Rotating turbines, propellers or screw propellers